Tributyltin Reduction in Constructed Wetland - Ophithakorn, Thiwari; Chetpattananondh, Pakamas; Yaeed, Sutisa (Burapha Science Journal, 2026)
The objective of this study is to investigate the influence of components in constructed wetland including water, sediment microorganisms and plants in tributyltin treatment and show important mechanisms from various components of the system including oxidation, settling and accumulation of sediment microorganisms and plant uptake. The results showed that the change of tin concentration in all laboratory experiments was occurred for 48 hours and then turned to equilibrium. After 1.3 days of treatment in the constructed wetland tin was found to be not exceed 1%, tin was absorbed by plant 13% and settling of tin and adsorption on sludge were over 76%. Therefore, the composition of the constructed wetland in terms of sediment microorganisms and settling and accumulation were the most influence mechanisms on tributyltin treatment followed by plant uptake and oxidation, respectively.